2018
DOI: 10.1093/mnras/sty3166
|View full text |Cite
|
Sign up to set email alerts
|

Optical andJ, K-photometry of the quiescent black hole X-ray nova A0620−00 in the passive and active states

Abstract: Photometric observations of the low-mass X-ray binary system A0620-00=V616 Mon are performed in the optical (unfiltered light, λ eff ≈ 6400Å) and the near-infrared J and K-bands. The mean system flux, the orbital light curve shape and the flickering amplitude dependences on wavelength are examined in the λλ6400 − 22000Å range for two activity stages of the system which remains in quiescence.In 2015-16 the A0620-00 system was observed to be in passive stage (according to the terminology of Cantrell et al., 2008… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 66 publications
2
10
0
Order By: Relevance
“…This "flickering" component is stronger at longer wavelengths, with a fractional rms amplitude of ∼ 15-24 per cent at optical wavelengths, rising to ∼ 42 per cent at (K-band) NIR wavelengths (Dinçer et al 2018). The spectral index of the variable component has been inferred by various authors to be steeply red at optical-NIR wavelengths (α = −1.4 to −0.7; Shahbaz et al 2004;Cantrell et al 2010;Dinçer et al 2018), and flat/slightly inverted at NIR (α ∼ 0.3 to 0.4; Cherepashchuk et al 2019) and mid-IR (α = 0.2 to 0.3 at 3.6-8.0 µm; Maitra et al 2011) wavelengths. Noting that the extrapolation of this non-stellar mid-IR spectrum of A0620-00 down to GHz frequencies was consistent with the radio flux measured by the VLA in 2005, Russell et al (2013a) concluded that the optically thick-to-thin jet break lies in the optical frequency range: 1.3 ± 0.5 × 10 14 Hz.…”
Section: A0620-00's Jet: Spectral Extent and Variabilitymentioning
confidence: 98%
See 2 more Smart Citations
“…This "flickering" component is stronger at longer wavelengths, with a fractional rms amplitude of ∼ 15-24 per cent at optical wavelengths, rising to ∼ 42 per cent at (K-band) NIR wavelengths (Dinçer et al 2018). The spectral index of the variable component has been inferred by various authors to be steeply red at optical-NIR wavelengths (α = −1.4 to −0.7; Shahbaz et al 2004;Cantrell et al 2010;Dinçer et al 2018), and flat/slightly inverted at NIR (α ∼ 0.3 to 0.4; Cherepashchuk et al 2019) and mid-IR (α = 0.2 to 0.3 at 3.6-8.0 µm; Maitra et al 2011) wavelengths. Noting that the extrapolation of this non-stellar mid-IR spectrum of A0620-00 down to GHz frequencies was consistent with the radio flux measured by the VLA in 2005, Russell et al (2013a) concluded that the optically thick-to-thin jet break lies in the optical frequency range: 1.3 ± 0.5 × 10 14 Hz.…”
Section: A0620-00's Jet: Spectral Extent and Variabilitymentioning
confidence: 98%
“…Figure 2. A0620-00's orbital-phased SMARTS V-band magnitudes, calculated using the updated ephemeris by Cherepashchuk et al (2019). Nearly simultaneous epochs with other multi-wavelength measurements quoted in the body of this paper are highlighted with different colors, and compared against the passive state "envelope" defined by Cantrell et al (2008), in black, vs. active state data from Cantrell et al, as well as Dinçer et al (2018), in sand and light pink.…”
Section: Smartsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be emphasised that in the optical light and in the IR range a considerable growing of the average brightness of the system was not accompanied by the increase of the flickering. In this feature KV UMa differed from the low mass X-ray nova A0620-00 (see, e.g., Shugarov et al 2016;Cherepashchuk et al 2019).…”
Section: Light Curvesmentioning
confidence: 90%
“…Recently it was realised that even in quiescence there are non-stationary processes in X-ray novae with black holes. They are manifested in the fact that some X-ray novae in quiescence show passive and active states of the optical variability (Cantrell et al 2008(Cantrell et al , 2010Cherepashchuk et al 2019). In the passive state the amplitude of the irregular variability (flickering) is relatively low, the orbital light curve has a regular shape.…”
mentioning
confidence: 99%